Media Pembelajaran Berbasis Vlog dalam Peningkatan Keterampilan Berbicara Bahasa Jerman - Fadhillah, Nur; Mannahali, Misnah; Rijal, Syamsu (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This study is a class action research that aims to determine the planning, implementation, and describe the results of the application of Vlog-based learning media in improving the speaking skills of students in class XI IPS 4 SMA Negeri 1 Maros. In this study there are two types of data, namely qualitative data which describes the results of implementation and observation during the teaching and learning process, as well as quantitative data which is the result of students' German speaking skills test. Based on the results of research from cycle I meeting 1, the observation results of the completeness of the implementation of teacher and student activities each reached 95%. At meeting 2, the observation results of the completeness of the implementation of teacher activities reached 100% and the completeness of the implementation of student activities reached 90%. There was an increase in observation results in cycle II. At meeting 1 the completeness of the implementation of teacher and student activities each reached 100%, at meeting 2 the completeness of the implementation of teacher activities reached 100% and the completeness of the implementation of student activities reached 95%. Based on the results of data analysis, the average score in cycle I was 67.20 and in cycle II there was an increase to 84.00. From the results of this study, it can be stated that Vlog-based learning media can improve students' German speaking skills.Keywords: Vlog Media, Speaking Skills, German